Microstreaming induced by acoustically trapped, non-spherically oscillating microbubbles. (25th September 2019) - Cleve, S.; Guédra, M.; Mauger, C.; Inserra, C.; Blanc-Benon, P.
Abstract : While numerous theoretical studies exist on microstreaming around acoustically excited, trapped gas bubbles, experimental approaches have mainly been conducted for bubbles attached to a solid boundary. One of the main difficulties lies in the positional stability of the microbubble. In the present work we trigger surface modes by bubble coalescence, with the advantage of limiting translational instabilities and controlling the orientation of the axisymmetric deformation. Furthermore, streaming is visualised by fluorescent tracer particles. In this way, bubble dynamics and streaming patterns can be studied together. Different types of streaming patterns are observed and correlated to the respective mode number. Besides the mode number, the bubble size and the phase difference between modal components are identified as important parameters in the definition of the pattern type.